From traditional public administration to the governance tradition research in NCPAG, 1952-2002 - Cariño, Ledivina V. (Philippine Journal of Public Administration, 2006)
The concept of "governance" has always been party to the study of public administration. The term "governance", however, has been used intensively and positively in relation to public administration only quite recently. This newly found prominence was in large part due to the efforts of the United Nations Development Programme (UNDP) which expoused it and gave it a definition in the mid-1990s. Ever so keen on the developments in the practice and study of public administration, the College of Public Administration followed the direction espoused by the UNDP and even adopted the term "governance" when it renamed itself as the National College of Public Administration and Governance (NCPAG) in 1998. Through a survey of researches, the development of the study of public administration and governance in what is now called the NCPAG is documented.